Jeeves and the leap of faith : a novel in homage to P.G. Wodehouse - Schott, Ben, 1974-; Wodehouse, P. G. (Pelham Grenville), 1881-1975 (Little, Brown and Company, 2020)
"Bertie and Jeeves are back for another spot of what Jeeves likes to call 'quiescent espionage' ... This time Bertie is required to impersonate a priest and journey to Cambridge, where the Seventh Earl of Sidcup, aspiring fascist Roderick Spode, is wooing undergraduates to his gang of Brown Shorts. Bertie accepts his charge with equanimity, even when required to do some 'nightclimbing' (an undergrad frolic involving skipping to and fro atop the towers of Trinity College). What's more problematic is the presence of Bertie's nemesis, the milk-drinking, obsessively matchmaking, all-around evildoing Aunt Agatha"--